Desensitization of Capsaicin-Sensitive Afferents Accelerates Early Tumor Growth via Increased Vascular Leakage in a Murine Model of Triple Negative Breast Cancer - Noémi Bencze; Noémi Bencze; Csaba Schvarcz; Gábor Kriszta; Gábor Kriszta; Lea Danics; Éva Szőke; Éva Szőke; Péter Balogh; Árpád Szállási; Péter Hamar; Péter Hamar; et al. (Frontiers in Oncology, 2021)
There is growing interest in the role of nerve-driven mechanisms in tumorigenesis and tumor growth. Capsaicin-sensitive afferents have been previously shown to possess antitumoral and immune-regulatory properties, the mechanism of which is currently poorly understood. In this study, we have assessed the role of these terminals in the triple negative 4T1 orthotopic mouse model of breast cancer. The ultrapotent capsaicin-analogue resiniferatoxin (RTX) was used for the selective, systemic desensitization of capsaicin-sensitive afferents. Growth and viability of orthotopically implanted 4T1 tumors were measured by caliper, in vivo MRI, and bioluminescence imaging, while tumor vascularity and protease enzyme activity were assessed using fluorescent in vivo imaging. The levels of the neuropeptides Calcitonin Gene-Related Peptide (CGRP), Substance P (SP), and somatostatin were measured from tumor tissue homogenates using radioimmunoassay, while tumor structure and peritumoral inflammation were evaluated by conventional use of CD31, CD45 and CD3 immunohistology. RTX-pretreated mice demonstrated facilitated tumor growth in the early phase measured using a caliper, which was coupled with increased tumor vascular leakage demonstrated using fluorescent vascular imaging. The tumor size difference dissipated by day seven. The MRI tumor volume was similar, while the intratumoral protease enzyme activity measured by fluorescence imaging was also comparable in RTX-pretreated and non-pretreated animals. Tumor viability or immunohistopathological profile was measured using CD3, CD31, and CD45 stains and did not differ significantly from the non-pretreated control group. Intratumoral somatostatin, CGRP, and SP levels were similar in both groups. Our results underscore the beneficial, antitumoral properties of capsaicin sensitive nerve terminals in this aggressive model of breast cancer, which is presumed to be due to the inhibition of tumor vascular bed disruption. The absence of any difference in intratumoral neuropeptide levels indicates non-neural sources playing a substantial part in their expression.